Wczesna opieka i edukacja dzieci w Polsce w kontekście europejskim - Brzezińska, Anna Izabela; Czub, Magdalena (My University, 2012)
The paper presents the contemporary approach to education understood as a process starting from the beginning of life. Describes the basic quality benchmarks of early childhood education and care and shows the status of the system existing in Poland, compared to solutions and requirements in Europe. It also indicates the need to introduce changes in Poland. Considering the need for change, the authors, in the analysis of the current system of early childhood education and care, suggest to use the U. Bronfenbrenner’s ecological approach to development and the P. B. Baltes’s concept of resources – SOC (selection, optimization, compensation).

Artykuł przedstawia współczesne podejście do edukacji ujmowanej jako proces rozpoczynający się od początku życia. Opisuje podstawowe wymogi jakości wczesnej edukacji i opieki nad dzieckiem i przedstawia stan istniejący w Polsce na tle rozwiązań i wymogów stosowanych w Europie. Wskazuje również na zmiany konieczne do wprowadzenia w Polsce. Rozpatrując potrzebę zmian, autorki, do analizy systemu wczesnej opieki i edukacji, proponują przyjęcie, za U. Bronfenbrennerem, podejścia ekologicznego oraz koncepcji SOC - P. B. Baltesa, dotyczącej modyfikacji zasobów – selekcji, optymalizacji i kompensacji.
Early childhood education and care in Poland in the European context
Keywords: Wczesne dzieciństwo; Wiek przedszkolny; Podzielony i zintegrowany system wczesnej opieki i edukacji; Selekcja; Optymalizacja; Kompensacja; Podejście siedliskowe; Early childhood; Preschool age; Split and unitary early care and education system; Selection; Optimization; Compensation; Settings approach